2020
DOI: 10.3324/haematol.2020.269878
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic characterization of COVID-19 patients with hematological cancer

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Limited data are available regarding the immunological landscape of COVID-19 in HM patients. A recent study [14] showed significantly decreased percentages of classical monocytes, immunoregulatory NK cells, double-positive T cells, and B cells, when compared to COVID-19 patients without HM.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Limited data are available regarding the immunological landscape of COVID-19 in HM patients. A recent study [14] showed significantly decreased percentages of classical monocytes, immunoregulatory NK cells, double-positive T cells, and B cells, when compared to COVID-19 patients without HM.…”
Section: Introductionmentioning
confidence: 92%
“…Limited data are available regarding the immunological landscape of COVID-19 in HM patients. A recent study [ 14 ] showed significantly decreased percentages of classical monocytes, immunoregulatory NK cells, double-positive T cells, and B cells, when compared to COVID-19 patients without HM. Another study [ 15 ] reported a protective effect of high CD8 + cell counts on COVID-19 related mortality, irrespective of the concomitant presence of B-cell deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Data analysis was performed as described elsewhere [ 49 , 50 ]. Briefly, it was based on a multi-step bioinformatics approach: (1) reading FCS data; (2) building a self-organizing map (SOM) for clustering; (3) performing a dimensionality reduction through principal component analysis (PCA) and uniform manifold approximation and projection (UMAP); (4) perform a supervised identification of each cluster; (5) performing a statistical analysis on the abundance of each population according to their origin (ANOVA).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical course and disease severity in COVID-19 is strongly associated with weaker immune response, bulk release of proinflammatory cytokines and the recruitment of neutrophils, monocytes and macrophages, which can generate an aggressive response, in some cases inappropriate, detrimental and harmful for the host [ 6 ], especially in cancer patients [ 7 , 8 ]. Recent reports disclosed the contribution of monocytes to the hyper-inflammatory phenotype, thus worsening disease severity [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients carrying hematological neoplasms have increased infection susceptibility, due to immunodeficiency, T-cell anergy, increased myeloid-derived suppressor cells and impairment of antigen presentation machinery [ 6 , 13 , 16 ], as a consequence of the malignancy itself. In multiple myeloma (MM), either anergic, dysfunctional effector lymphocytes or both, tumor-educated myeloid-derived suppressor cells and soluble mediators promote coordinately cancer immune-evasion [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%